Plainsong in the Age of Polyphony - Kelly, Thomas Forrest (Cambridge Cambridge University Press, 1992)
From at least the eighth century and for about a thousand years the repertory of music now known as Gregorian chant, or plainsong, formed the largest body of written music, and was the most frequently performed and the most assiduously studied music in Western civilisation. It lay at the root of all instruction in practical music, and in some sense was at the core of the enormous portion of notated music that survives today. But plainsong did not follow rigid conventions. It seems increasingly clear that, whatever may have been intended with respect to uniformity and tradition, the practice of plainsong varied considerably within time and place. It is just this variation, this living quality of plainsong, that these essays address. In addition, much new information is made available on the study of local rites and practices, and on the liturgical matrix of important polyphonic repertories. The contributors - leading scholars in their field - have sought information from a wide variety of areas: liturgy, architecture, art history, secular and ecclesiastical history, and hagiography, as a step towards reassembling the fragments of cultural history into the rich mosaic from which they came.
Keywords: Past; Plainchant; Music history